2001
DOI: 10.1046/j.1365-2869.2001.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 1 week of REM sleep deprivation on parvalbumin and calbindin immunoreactive neurons in central visual pathways of kittens

Abstract: Many maturational processes in the brain are at high levels prenatally as well as neonatally before eye‐opening, when extrinsic sensory stimulation is limited. During these periods of rapid brain development, a large percentage of time is spent in rapid eye movement (REM) sleep, a state characterized by high levels of endogenously produced brain activity. The abundance of REM sleep in early life and its ensuing decline to lower levels in adulthood strongly suggest that REM sleep constitutes an integral part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…These studies suggest that at least some effects of REM sleep deprivation on LGN cell size are mediated by the phasic processes of REM sleep. Another interesting result showed that REM sleep deprivation for 1 week decreased immunoreactivity for the calcium binding protein parvalbumin, which has been demonstrated to influence certain forms of neuronal synaptic plasticity [50], in GABAergic inter-neurons of the developing LGN [51]. Therefore, all these studies indicate that REM sleep may influence plasticity in the LGN during critical periods of visual system development [52].…”
Section: Rem Sleepmentioning
confidence: 93%
“…These studies suggest that at least some effects of REM sleep deprivation on LGN cell size are mediated by the phasic processes of REM sleep. Another interesting result showed that REM sleep deprivation for 1 week decreased immunoreactivity for the calcium binding protein parvalbumin, which has been demonstrated to influence certain forms of neuronal synaptic plasticity [50], in GABAergic inter-neurons of the developing LGN [51]. Therefore, all these studies indicate that REM sleep may influence plasticity in the LGN during critical periods of visual system development [52].…”
Section: Rem Sleepmentioning
confidence: 93%
“…This is an evidence that REM sleep facilitates the development of neuronal receptors that are associated with synaptic plasticity. 126 Additional evidence of the role of both NREM and REM sleep on ocular dominance plasticity was demonstrated in a series of four-kitten experiments. 127 This experiment used a shaking cage technique for generalized sleep deprivation.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 92%
“…The surgical procedure was carried out according to previously published protocols described here briefly (Oksenberg et al, 1996; Shaffery et al, 1998; Hogan et al, 2001). Animals were anesthetized with pentobarbital (40 mg/kg i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Our computer-controlled system for detection as well as deprivation of REMS was modified from a previously reported technique (Shaffery et al, 1990; Hogan et al, 2001). The system reliably identifies REMS on the basis of individually determined, minimum-amplitude threshold criteria configured from each kitten’s digitized ECoG and EMG recordings.…”
Section: Methodsmentioning
confidence: 99%